Hierarchy and Scale Influence the Western Monarch Butterfly Overwintering Microclimate - Saniee, Kiana; Villablanca, Francis (Frontiers in Conservation Science, 2022)
Migratory species are expected to demonstrate habitat selection that occurs at multiple spatial and temporal scales. Western monarch butterflies migrate seasonally to overwintering groves at geographically predictable locations along the California coast. To date, overwintering habitat selection by western monarch butterflies has primarily been studied assuming the microclimate hypothesis. Specifically, that habitat selection occurs when monarchs form dense overwintering aggregations within overwintering groves. But western monarch butterflies are migratory, thus previous habitat selection studies could have commingled selection at different scales into a single spatial scale at the aggregation site. Therefore, we explore monarch overwintering habitat selection to determine whether an explicit spatial framework is necessary. We studied nine groves on the coast of California and at each we collected temperature, humidity, and light data from grove edges, grove interiors, and aggregation locations over several weeks of the overwintering season. We tested the hypothesis that monarchs aggregate in locations within groves that have consistent attributes across groves (the microclimate hypothesis). We find neither evidence supporting the hypothesis that the aggregation locations have a unique microclimate that differs significantly from other locations inside the grove nor that aggregation locations are uniform in their microclimatic attributes across overwintering groves. Rather, we find that microclimatic attributes at the aggregation locations vary spatially with latitude and that aggregation conditions exist in a large portion of each grove. We conclude that it will be necessary to consider spatial effects when studying or managing western monarch butterfly overwintering habitat and that interpretations of habitat selection to date likely commingled habitat selection at multiple spatial scales.